Irritable bowel syndrome with food‐related symptoms: Future directions in the clinical management. Issue 6 (21st June 2022) - Melchior, Chloé; Algera, Joost; Colomier, Esther; Törnblom, Hans; Simrén, Magnus
Abstract: The majority of patients with irritable bowel syndrome (IBS) experiences food‐related symptoms, which are associated with high symptom burden, reduced quality of life, increased healthcare consumption and reduced intake of certain nutrients. In this review we aimed to describe a clinically useful approach for physicians, by presenting the latest progress in knowledge and its translation to management in IBS patients with food‐related symptoms, as well as the underlying mechanisms involved. The research tools currently available that can be used in the future for a better characterization of this subgroup of patients are also discussed. Working towards this approach could lead to a more individualised work‐up and management of IBS patients with food‐related symptoms.